A Semantics for Concurrent Logic Programming Languages Based on Multiple-Valued Logic - Glazerman, Marion (International journal of advanced computer science & applications, 2012)
In order to obtain an understanding of parallel logic thought it is necessary to establish a fully abstract model of the denotational semantics of logic programming languages. In this paper, a fixed point semantics for the committed choice, non-deterministic family of parallel programming languages, i.e. the concurrent logic programming languages is developed. The approach is from an order theoretic viewpoint. We rigorously define a semantics for a Guarded Horn Clauses-type of language because of the minimal restrictions of the language. The extension to other concurrent logic programming languages would be direct and analogous, based on their specific rules of suspension. Today’s world is replete with multitasking and parallelism in general. The content of this paper reflects a paradigm of an application of multi-valued logic which is reflective of this.